Inflammatory response: The target for treating hyperpigmentation during the repair of a burn wound - Zhong, Chi; Liang, Geao; Li, Peiting; Shi, Ke; Li, Fuyin; Zhou, Jianda; Xu, Dan (Frontiers in Immunology, 2023)
Hyperpigmentation is a common complication in patients with burn injuries during wound healing; however, the mechanisms underlying its occurrence and development remain unclear. Recently, postinflammatory hyperpigmentation (PIH) was found to result from overproduction of melanin. Local or systemic inflammatory responses are often observed in patients who develop hyperpigmentation. However, we lack studies on the relationship between PIH and burn injury. Therefore, we comprehensively reviewed the existing literature on the melanogenesis of the skin, inflammatory mechanisms in pigmentation, and local or systemic alteration in inflammatory cytokines in patients suffering from burn trauma to elucidate the relationship between PIH and burn injury. We believe this review would guide further research on regulating melanin production in the burn management process.